2012
DOI: 10.1016/j.ajpath.2012.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Expression of Interferon-γ in Mouse Stomach Leads to Inflammation, Metaplasia, and Dysplasia

Abstract: Gastric adenocarcinoma is one of the leading causes of cancer mortality worldwide. It arises through a stepwise process that includes prominent inflammation with expression of interferon-γ (IFN-γ) and multiple other pro-inflammatory cytokines. We engineered mice expressing IFN-γ under the control of the stomach-specific H(+)/K(+) ATPase β promoter to test the potential role of this cytokine in gastric tumorigenesis. Stomachs of H/K-IFN-γ transgenic mice exhibited inflammation, expansion of myofibroblasts, loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 47 publications
3
45
2
Order By: Relevance
“…In the gastric mucosa after 3 weeks of infection, areas of inflammation and SPEM were visible and in some cases extensive (Figure 3) but were interspersed with patches of normal-appearing mucosa. Consistent with previous reports [36], SPEM in infected mice was characterized by the loss of specialized gland cells and expansion of metaplastic cells with abundant, “foamy” mucin-filled cytoplasm that stained purple/blue with periodic acid–Schiff/Alcian blue (Figure 3).
Figure 3.Infection with SS1 s1i1 induces spasmolytic polypeptide-expressing metaplasia (SPEM) and inflammation in mouse gastric mucosa.
…”
Section: Resultssupporting
confidence: 92%
“…In the gastric mucosa after 3 weeks of infection, areas of inflammation and SPEM were visible and in some cases extensive (Figure 3) but were interspersed with patches of normal-appearing mucosa. Consistent with previous reports [36], SPEM in infected mice was characterized by the loss of specialized gland cells and expansion of metaplastic cells with abundant, “foamy” mucin-filled cytoplasm that stained purple/blue with periodic acid–Schiff/Alcian blue (Figure 3).
Figure 3.Infection with SS1 s1i1 induces spasmolytic polypeptide-expressing metaplasia (SPEM) and inflammation in mouse gastric mucosa.
…”
Section: Resultssupporting
confidence: 92%
“…35 Using a similar model to overexpress IFNγ, Syu et al reported IFNγ induced metaplasia. 38 In the present study, L635-treated IFNγKO mice developed SPEM similar to wild type mice. The difference in our findings may depend on experimental conditions used to induce parietal cell loss.…”
Section: Discussionsupporting
confidence: 62%
“…25,26 Notably, there is considerable evidence that elevated expression of IL-1β, IFN-γ, and TNF-α are associated with chronic gastritis and gastric cancer development following HP infection. 7,11,25,27,28 Our study revealed that OPN expression was elevated in response to HP infection, and OPN depletion decreased production of these cytokines in both gastric epithelial cells and macrophages during HP infection. These results suggest that OPN is an important mediator of proinflammatory cytokine production during HP infection.…”
Section: Discussionmentioning
confidence: 88%